Efektivitas Media Interaktif Animasi Berbasis Kahoot Terhadap Minat Belajar Siswa pada Mata Pelajaran IPAS Kelas 3 SD Negeri 3 Purwawinangun - Sari, Dita Komala; Salam, Dudung Abdu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research endeavors to examine the efficacy of employing Kahoot-integrated interactive animated tools to stimulate the learning enthusiasm of third-grade pupils at SD Negeri 3 Purwawinangun in the subjects of Science and Social Studies (IPAS). The method used in this study was quantitative with a non-equivalent control group design. The study encompasses 40 students, categorized into both experimental and control divisions. The instruments utilized for gathering data encompass surveys gauging learning interest, observational assessments, dialogues with participants, and documentary evidence. Analytical procedures applied to the data encompass normality assessments, homogeneity evaluations, an autonomous sample t-test analysis, and computations of N-Gain scores. The results indicate marked variations in learning interest levels between pupils exposed to Kahoot-supported interactive animated resources and those educated via standard methodologies. This medium has been validated to amplify student participation, encourage energetic involvement, and cultivate an agreeable educational atmosphere. Thus, the employment of Kahoot-integrated interactive animated tools is demonstrably effective in elevating students’ eagerness to learn IPAS within the context of primary education.